Quantifying Benefits of Sustainability Agreements under Article 101 TFEU in terms of Human Well-Being - Eva van der Zee (University of Hamburg, Institute of Law and Economics (ILE), 2020)
The main aim of this paper is to examine how the current European Commission guidelines issued in 2004 on the application of Article 101(3) of the Treaty on the Functioning of the European Union (TFEU) (hereinafter: Commission guidelines) could be improved to allow undertakings to assess their agreements under Article 101(3) TFEU in a way that is quantifiable but that goes beyond an economic approach focusing solely on monetary well-being. This research is timely, as the Commission is currently reviewing the Horizontal Block Exemption Regulations and the Horizontal Co-operation Agreements Guidelines. To achieve this aim, I will first give a brief overview of Article 101 TFEU and the Commission guidelines, pointing out where further guidance is needed. Then, I will show that based on communications by the Commission, as well as based on case law by the Court of Justice of the European Union (CJEU), the term "benefits" under Article 101(3) TFEU should be interpreted as a wide notion of well-being (ie not solely related to monetary well-being), also known as HWB. Based on the legal analysis, this paper explores different methods to estimate HWB (economic cost-benefit analysis, well-being analysis, resourcism, and the capabilities approach), arguing that a combination of these methods would provide the most accurate estimation of HWB. It is concluded that, in the right hands with the proper understanding of the strengths and weaknesses, statistical data derived from HWB methods can provide important insights. To improve guidance as to how to use these insights, national agencies or the European Commission are advised to answer normative questions. These questions include which discount rate should be chosen and which capabilities society deems important.
Keywords: K21; L4; 330; competition law; European law; human well-being